Efekty wdrażania nowoczesnych struktur i metod zarządzania w polskiej energetyce na przykładzie BOT Elektrownia Bełchatów SA - Różański, Jerzy (The Effects of Implement Management Modern Structures and Methods on Energetic Sector Example, 2006)
The article represents the methods of rationalization management structures and systems in Polish energy on the example of Elektrownia Bełchatów and ВОТ Górnictwo i Energetyka SA group. Stability of working rules and market reliability have had a positive influence on the activity of the energetic sector's modules, at the extent of adjustment the structures and methods of management. Outsourcing was applied, controlling and many elements of lean management's conceptions were developed in the widest sphere. On the general assessment, the positive innovation's effects are more predominant than negatives - the effectiveness of these elements, in board interpretation, is increasing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 457-463